Mechanizm gospodarki rzeczowej a funkcjonowanie gospodarki pieniężnej - Wilczyńska, Kamila (Wydział Prawa i Administracji UAM, 1989)
The reforms carried out nowadays must overcome numerous prejudices connected with the role of money nad market in modern economy. Market mechanism is interpreted as a symbol of anarchy of production, with money as an object of cult. Therefore, it seems necessary to present and arrange basic notions connected with material and monetary economy. The experiences of material economy on one hand and monetary economy on the other point to a clear advantage of the latter in structural and long-term undertakings. Namely inefficiency of material economy leads to shortening the time range of planning and to „ad hoc" decisions forced by circumstances as well as to neglecting the environmental protection and wasteful exploitation of natural resources. At the same time countries with monetary-market economy implement large, long-term infrastructural investment on a scale unheard-of socialist countries. The possibilities of conscious shaping the developmental processes in agreement with social interest do not depend upon the existence of material economy; on the contrary, they require that material economy be overcome. The above does not mean that social character of economy has to be given up.
The mechanism of material economy and the functioning of monetary economy